Thermoregulation during intermittent exercise in athletes with a spinal-cord injury - Griggs, K. E.; Leicht, C. A.; Price, M. J.; Goosey-Tolfrey, V. L. (International Journal of Sports Physiology and Performance, 2015)
Purpose: Individuals with a spinal-cord injury have impaired thermoregulatory control due to a loss of sudomotor and vasomotor effectors below the lesion level. Thus, individuals with high-level lesions (tetraplegia) possess greater thermoregulatory impairment than individuals with lower-level lesions (paraplegia). Previous research has not reflected the intermittent nature and modality of wheelchair court sports or replicated typical environmental temperatures. Hence, the purpose of this study was to investigate the thermoregulatory responses of athletes with tetraplegia and paraplegia during an intermittent-sprint protocol (ISP) and recovery in cool conditions. Methods: Sixteen wheelchair athletes, 8 with tetraplegia (TP, body mass 65.2 ± 4.4 kg) and 8 with paraplegia (body mass 68.1 ± 12.3 kg), completed a 60-min ISP in 20.6°C ± 0.1°C, 39.6% ± 0.8% relative humidity on a wheelchair ergometer, followed by 15 min of passive recovery. Core temperature (Tcore) and mean (Tsk) and individual skin temperatures were measured throughout. Results: Similar external work (P = .70, ES = 0.20) yet a greater Tcore (P < .05, ES = 2.27) and Tsk (P < .05, ES = 1.50) response was demonstrated by TP during the ISP. Conclusions: Despite similar external work, a marked increase in Tcore in TP during exercise and recovery signifies that thermoregulatory differences between the groups were predominantly due to differences in heat loss. Further increases in thermal strain were not prevented by the active and passive recovery between maximal-effort bouts of the ISP, as Tcore continually increased throughout the protocol in TP.